Answer:
v =7
Step-by-step explanation:
Simplifying
v + -10 = -3
Reorder the terms:
-10 + v = -3
Solving
-10 + v = -3
Solving for variable 'v'.
Move all terms containing v to the left, all other terms to the right.
Add '10' to each side of the equation.
-10 + 10 + v = -3 + 10
Combine like terms: -10 + 10 = 0
0 + v = -3 + 10
v = -3 + 10
Combine like terms: -3 + 10 = 7
v = 7
Simplifying
v = 7
Answer:
3/20
Step-by-step explanation:
3 x 1/4 x 1/5 = 3/20
1st find the midpoint
-3 + 3 = 0/2 = 0 for the x
2 + 2 = 4/2 = 4 for the y
the midpoint is (0,2) which is along the y-axis which is your answer
Answer:
Exponent laws:
1. Product law

In product law if bases are same then we add their respective powers.But if bases are different we can't add their powers.
x=base, a,b,c=exponent
If x=2 and a=3, b=5 , and c=10, then

2.Product raised to a power
1. ![[x^{a}]^{c}=x^{ac}](https://tex.z-dn.net/?f=%5Bx%5E%7Ba%7D%5D%5E%7Bc%7D%3Dx%5E%7Bac%7D)
2. ![[x^{a}\times x^{b}]^{c}=[x^{a+b}]^{c}=x^{ac+bc}](https://tex.z-dn.net/?f=%5Bx%5E%7Ba%7D%5Ctimes%20x%5E%7Bb%7D%5D%5E%7Bc%7D%3D%5Bx%5E%7Ba%2Bb%7D%5D%5E%7Bc%7D%3Dx%5E%7Bac%2Bbc%7D)
If product is raised to a certain power , keeping the base same , we just multiply the powers.for example
and
![[2^{3}\times3^{2}]^{2}=[2^{3}]^2 \times[3^{2}]^{2}=2^{6}\times3^{4}](https://tex.z-dn.net/?f=%5B2%5E%7B3%7D%5Ctimes3%5E%7B2%7D%5D%5E%7B2%7D%3D%5B2%5E%7B3%7D%5D%5E2%20%5Ctimes%5B3%5E%7B2%7D%5D%5E%7B2%7D%3D2%5E%7B6%7D%5Ctimes3%5E%7B4%7D)
![[2^{3}\times2^{2}]^{2}=[2^{3+2}]^{2}=[2^{5}]^{2}=2^{10}](https://tex.z-dn.net/?f=%5B2%5E%7B3%7D%5Ctimes2%5E%7B2%7D%5D%5E%7B2%7D%3D%5B2%5E%7B3%2B2%7D%5D%5E%7B2%7D%3D%5B2%5E%7B5%7D%5D%5E%7B2%7D%3D2%5E%7B10%7D)
Answer:
1 + 72 ÷4 × 2 =10 with brackets it equals 10
1 + (72 ÷ (4 × 2)) =10
Step-by-step explanation: